2008
DOI: 10.1094/ats-2008-0916-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

‘Riviera’ Bermudagrass Response to Pre-seeding Applications of Sulfonylurea Herbicides

Abstract: Recent advancements in cold tolerance of seeded bermudagrass cultivars have allowed seeding to repair thin areas following winter kill. Areas devoid of bermudagrass are often unnoticed until herbicides are applied to remove perennial ryegrass and winter weeds from golf course fairways and athletic fields. Trials were conducted in Blacksburg, VA, with flazasulfuron, foramsulfuron, metsulfuron, rimsulfuron, sulfosulfuron, and trifloxysulfuron‐sodium at 35, 28, 42, 35, 34, and 29 g ai/ha, respectively, applied 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Williams and Burrus (29) suggested that the most effective means of converting perennial ryegrass to seeded bermudagrass was to seed after applying either glyphosate or pronamide, which significantly reduced competition from the perennial ryegrass. Willis et al (31) found that applying sulfonylurea herbicides before seeding bermudagrass had minimal effects on the establishment of seeded bermudagrass. Although that study suggests that chemical transition and seeding could be accomplished simultaneously, this has not been tested as a viable means of establishing seeded bermudagrass during the dormant period.…”
Section: Background and Rationale For The Studymentioning
confidence: 99%
“…Williams and Burrus (29) suggested that the most effective means of converting perennial ryegrass to seeded bermudagrass was to seed after applying either glyphosate or pronamide, which significantly reduced competition from the perennial ryegrass. Willis et al (31) found that applying sulfonylurea herbicides before seeding bermudagrass had minimal effects on the establishment of seeded bermudagrass. Although that study suggests that chemical transition and seeding could be accomplished simultaneously, this has not been tested as a viable means of establishing seeded bermudagrass during the dormant period.…”
Section: Background and Rationale For The Studymentioning
confidence: 99%
“…Researchers noted that trifloxysulfuron applied one week before seeding injured bermudagrass greater than 30% and reduced establish-ment (Willis et al, 2007). Foramsulfuron, metsulfuron, and sulfosulfuron were reported safe to apply one or three weeks after seeding but rimsulfuron caused significant bermudagrass injury (Willis et al, 2008). In Arkansas, injury to bermudagrass seedlings was reported from MSMA applications with flazasulfuron, foramsulfuron, metribuzin, or trifloxysulfuron, but injury was temporary and generally did not reduce overall bermudagrass establishment after 30 days (Richardson et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…ex Muhl.) [27], annual bluegrass (Poa annua L.), and perennial ryegrass [11,15]. Furthermore, Brecke et al [25] reported that flazasulfuron 0.05 kg a.i.…”
Section: Weed Controlmentioning
confidence: 99%